Implementation of learners' science process skills by primary school teachers in the Lejweleputswa District of South Africa: A case study - Ritu Bhagwandeen; Mrs Shirley Moopeloa; Awelani Melvin Rambuda (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2024)
This research explores teachers' perceptions of the development of learners' science process skills through the implementation of inquiry-based approaches in Thabong primary schools in the Lejweleputswa District, South Africa. Its aim was to find effective teaching methods using inquiry-based approaches to develop learners' science process skills and improve their scientific literacy. This quantitative study was conducted with natural sciences and technology, natural sciences, and mathematics teachers, and data was analysed using SPSS 27. The results showed a statistically significant relationship between inquiry-based approaches and learners' acquisition of science process skills. Although teachers understood the advantages of using inquiry-based teaching, there were many obstructions to the implementation of this in classrooms in the schools used in this study.